Elaboração de material pré-composicional através de expansão de procedimentos do sistema Schillinger de composição musical - Morais Júnior, Agamenon Clemente de (2014)
The work aims at investigating possibilities of extending compositional procedures, based on the Schillinger System of Musical Composition (SSMC). I start by elaborating a brief historical review on SSMC, which is followed by a critical review of the System. The work includes a state of the art on the research on this topic, performed upon analysis of the current work conducted by a research group from the UFRN Music School from which I also make part. The main line of the research is to elaborate on the suggestion of extending the SSMC concept of place of attack to the idea of place of instrumentation, through developing a binary instrumentation procedure. The experimentation on the thesis‟ hypothesis is presented in my composition titled “Suíte Grega” (Greek Suite), a compositional memoir for Oboe, Saxophone and 3 Cellos.